“THE IMPACT OF FILM AND SERIES SUBTITLES ON STUDENTS’ UNDERSTANDING OF FOREIGN LANGUAGES” - Riska Sari; Nurul Nisa; Ratu Yulianti Natsir; Sitti Maryam Hamid (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to investigate the relationship between the use of film subtitles and students’ translation ability. A quantitative approach with a correlational design was employed, involving 31 students from the English Language Education program who had been exposed to translation theory and regularly watched foreign-language films with subtitles. The data were collected using a closed-ended questionnaire in the form of a Likert scale, consisting of 20 items that measured both the frequency of subtitle use and translation ability. After testing for normality, the data were analyzed using Spearman’s rank correlation due to its ordinal nature. The results revealed a moderate positive correlation (r = 0.449) between the use of subtitles and translation ability, with a significance value of 0.013 (p < 0.05), indicating a statistically significant relationship. These findings suggest that subtitles can serve as an effective medium to support language learning, especially in enhancing students’ understanding of vocabulary, sentence structure, and context in translation. This study highlights the potential of integrating multimedia tools like film subtitles into language education to improve students' translation competence.